2020
DOI: 10.1093/jnci/djaa116
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Body Mass Index in Metastatic Breast Cancer Patients Treated With Abemaciclib and Endocrine Therapy

Abstract: Background There are limited data regarding the impact of body mass index (BMI) on outcomes in advanced breast cancer, especially in patients treated with endocrine therapy (ET) + cyclin-dependent kinase 4/6 inhibitors. Methods A pooled analysis of individual patient-level data from MONARCH 2 and 3 trials was performed. Patients were classified according to baseline BMI into underweight (<18.5 kg/m2), normal (18.5-24.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 56 publications
5
26
2
Order By: Relevance
“…Nonetheless, our study, which uses a much larger pooled clinical trial cohort, demonstrated contrasting results of pretreatment overweight/obese BMI being independently associated with improved survival outcomes in HER2 positive ABC. The cause of the difference between our study and Krasniqi et al 26 as well as between other ABC studies indicating a paradox 30,32 , that there is no BMI association 30,31,34,35 , or that high BMI is associated with poor outcomes [26][27][28][29] remains unknown; however, it does highlight the need for further investigation. In strength to the study herein the obesity paradox demonstrated was consistently observed across the four pooled HER2 positive ABC clinical trials (Supplementary Table 6).…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…Nonetheless, our study, which uses a much larger pooled clinical trial cohort, demonstrated contrasting results of pretreatment overweight/obese BMI being independently associated with improved survival outcomes in HER2 positive ABC. The cause of the difference between our study and Krasniqi et al 26 as well as between other ABC studies indicating a paradox 30,32 , that there is no BMI association 30,31,34,35 , or that high BMI is associated with poor outcomes [26][27][28][29] remains unknown; however, it does highlight the need for further investigation. In strength to the study herein the obesity paradox demonstrated was consistently observed across the four pooled HER2 positive ABC clinical trials (Supplementary Table 6).…”
Section: Discussioncontrasting
confidence: 89%
“…Association between BMI and survival outcomes in HER2 positive ABC Data was available for 3496 HER2 positive ABC patients, of which 35 months [34][35][36] in MARIANNE, 47 months [46][47][48][49] in EMILIA, and 35 months [34][35][36] 2). Supplementary Table 5 outlines univariable analysis describing the association between BMI category and survival outcomes.…”
Section: Associationmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, body composition parameters may influence the prognosis in patients receiving CDK4/6 inhibitors. In a retrospective study, baseline sarcopenia (skeletal muscle index <40) was retrospectively associated with a significantly worse PFS, whereas a high visceral fat index and higher visceral fat density were associated with better PFS [ 64 ].…”
Section: Future Perspectivesmentioning
confidence: 99%